Science Fiction Theology: Beauty and the Transformation of the Sublime by Alan P. R. Gregory - Delport, Khegan (Stellenbosch Theological Journal, 2023)
This is quite simply a marvellous book. In Science Fiction Theology, Alan Gregory has given a model for responsible theological engagement with both literature and pop culture. His vast knowledge and patient exposition of science fiction (SF) and his ability, moreover, to weave deep readings of SF within a sophisticated account of Christian metaphysics are certainly enviable. Those who attempt similar projects of comparison should definitely take notice; reverse-engineering its composition would be worthwhile for any author in the genre.